2014
DOI: 10.1186/1471-2164-15-s7-s6
|View full text |Cite
|
Sign up to set email alerts
|

Linkage disequilibrium and haplotype block structure in a composite beef cattle breed

Abstract: BackgroundThe development of linkage disequilibrium (LD) maps and the characterization of haplotype block structure at the population level are useful parameters for guiding genome wide association (GWA) studies, and for understanding the nature of non-linear association between phenotypes and genes. The elucidation of haplotype block structure can reduce the information of several single nucleotide polymorphisms (SNP) into the information of a haplotype block, reducing the number of SNPs in a coherent way for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 37 publications
2
42
1
1
Order By: Relevance
“…O'Brien et al (2014) showed that r 2 values above 0.3 were required to give sufficient power in genome wide association studies (GWAS). In the current study, r 2 values above 0.2 were achieved at a distance less than 70 kb between adjacent markers, indicating that using BovineSNP50K BeadChip with marker interval 67.8 kb is inconsistent for achieving a high accuracy of genomic breeding values and Recently, high density (HD) chips have been used in GWAS (Mokry et al 2014;O'Brien et al 2014;Nayeri et al 2016) and a marker interval of 5 kb can be obtained from such SNP density provided that r 2 reaches 0.59 in taurine species (O'Brien et al 2014). Consequently, the HD chip could be more appropriate for GWAS than the 50K chip.…”
Section: Resultsmentioning
confidence: 67%
“…O'Brien et al (2014) showed that r 2 values above 0.3 were required to give sufficient power in genome wide association studies (GWAS). In the current study, r 2 values above 0.2 were achieved at a distance less than 70 kb between adjacent markers, indicating that using BovineSNP50K BeadChip with marker interval 67.8 kb is inconsistent for achieving a high accuracy of genomic breeding values and Recently, high density (HD) chips have been used in GWAS (Mokry et al 2014;O'Brien et al 2014;Nayeri et al 2016) and a marker interval of 5 kb can be obtained from such SNP density provided that r 2 reaches 0.59 in taurine species (O'Brien et al 2014). Consequently, the HD chip could be more appropriate for GWAS than the 50K chip.…”
Section: Resultsmentioning
confidence: 67%
“…The correlation of the r value represents the degree of genetic relationship between populations (Mokry et al, 2014). In our study, the persistence of LD phase between Simmental and Wagyu was over 0.80 at a genomic distance o100 kb (Table 1), and decreased to a minimum of 0.51 extending to a genomic distance of 500 kb.…”
Section: Ld Decay Persistence Of Ld Phase and Ancestral Effective Posupporting
confidence: 47%
“…Previous studies reported the haplotype block properties in cattle could be influenced by many aspects, such as breed, marker types, marker density and chromosome region, which formed average haplotype block size from 5.7 kb (2 or more SNPs) to 700 kb (hundreds of SNPs) (Gautier et al, 2007;Villa-Angulo et al, 2009). Another study used the BovineHD Beadchip to identify haplotype blocks in a composite beef cattle breed, and they reported the block coverage length with 1569.5 Mb across the genome, 76,673 haplotype blocks (61% genome) with 77% SNPs covered in haplotype blocks (Mokry et al, 2014). Compared with the study presented by Mokry et al, we observed the number of blocks was larger in Chinese Simmental (84,322), while was smaller in Wagyu (73,915), and we also found the block coverage length and percentage of SNPs in block were relatively smaller in both populations.…”
Section: Haplotype Block Structurementioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the LD pattern in a population is the basis for genomic prediction, genome-wide association studies (GWAS), and quantitative trait loci (QTL) mapping for complex traits. The extent of LD has been examined in diverse taxa, including pigs (Amaral et al 2008; Badke et al 2012), horses (Corbin et al 2010), cattle (Khatkar 2008; Mokry et al 2014), and chickens (Qanbari et al 2010). In the study of sheep, LD has been estimated using microsatellite markers across the genome in the early stage (Meadows et al 2008).…”
Section: Introductionmentioning
confidence: 99%